Testing the Extreme Male Brain Hypothesis: Is Autism Spectrum Disorder Associated with a More Male-Typical Brain? - van Eijk, Liza (Autism Res, 2021)
Autism Spectrum Disorder (ASD) is more common in males than females and has been linked to male-typical behavior. Accordingly, the ‘Extreme Male Brain’ hypothesis suggests that ASD is associated with an exaggeratedly male-typical brain. To test this hypothesis, we derived a data-driven measure of individual differences along a male-female dimension based on sex differences in subcortical brain shape (i.e. brain maleness) by training our algorithm on two population samples (Queensland Twin Imaging study and Human Connectome Project; combined N=2,153). We then applied this algorithm to two clinical datasets (Autism Brain Imaging Data Exchange I and II; ASD N=1,060; neurotypical controls N=1,166) to obtain a brain maleness score for each individual, representing maleness of their brain on a male-female continuum. Consistent with the Extreme Male Brain hypothesis, we found a higher mean brain maleness score in the ASD group than in controls (d=0.20 (0.12–0.29)), parallel to higher scores for control males than control females (d=1.17 (1.05–1.29)). Further, brain maleness was positively associated with autistic symptoms. We tested the possibility this finding was driven by the ASD group’s larger brains than controls (d= 0.17 (0.08–0.25)), given that males had larger brains than females (d= 0.96 (0.84–1.07)). Indeed, after adjusting for differences in brain size, the brain maleness difference between the ASD group and controls disappeared, and no association with autistic symptoms remained (after controlling for multiple comparisons), suggesting greater maleness of the autistic brain is driven by brain size. Brain maleness may be influenced by the same factors that influence brain size.